2008
DOI: 10.1162/jocn.2008.20117
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms Underlying Adaptive Actions after Slips

Abstract: Abstract& An increase in cognitive control has been systematically observed in responses produced immediately after the commission of an error. Such responses show a delay in reaction time (post-error slowing) and an increase in accuracy. To characterize the neurophysiological mechanism involved in the adaptation of cognitive control, we examined oscillatory electrical brain activity by electroencephalogram and its corresponding neural network by event-related functional magnetic resonance imaging in three exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
132
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(152 citation statements)
references
References 64 publications
17
132
2
1
Order By: Relevance
“…In imaging studies, activations ipsilateral to the motor response have been observed during the performance of complex motor tasks (Banich, 1998;Verstynen et al, 2005;Welcome and Chiarello, 2008). Previous studies have shown that the commission of an error engaged several regions involved in performance monitoring which resulted in either decreased activation or increased inhibition of the contralateral motor cortex (Marco-Pallare´s et al, 2008;Danielmeier and Ullsperger, 2011), which presumably might lead to the increase of excitability of the ipsilateral motor cortex shown in our data. Indeed, the reciprocal activation/ inhibition of the two hemispheres is thought to be mediated via transcallosal connections featuring inhibitory GABA B receptors (Irlbacher et al, 2007;Palmer et al, 2012).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In imaging studies, activations ipsilateral to the motor response have been observed during the performance of complex motor tasks (Banich, 1998;Verstynen et al, 2005;Welcome and Chiarello, 2008). Previous studies have shown that the commission of an error engaged several regions involved in performance monitoring which resulted in either decreased activation or increased inhibition of the contralateral motor cortex (Marco-Pallare´s et al, 2008;Danielmeier and Ullsperger, 2011), which presumably might lead to the increase of excitability of the ipsilateral motor cortex shown in our data. Indeed, the reciprocal activation/ inhibition of the two hemispheres is thought to be mediated via transcallosal connections featuring inhibitory GABA B receptors (Irlbacher et al, 2007;Palmer et al, 2012).…”
Section: Discussionsupporting
confidence: 65%
“…A direct relationship between our findings at 450 ms and the error detection processes indexed by the ERN might be unlikely since the peak of this ERP component appears before 100 ms post-response (e.g., Rodrı´guez-Fornells et al, 2002). A neurophysiological marker more closely associated in time with our TMS finding is the error-related oscillatory brain activity observed by Marco-Pallare´s et al (2008). In this multimodal study, a frontocentral increase of beta power starting at about 400-500 ms after an erroneous response showed a positive correlation with PES on the next correct trial.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Consequently, CMT predicts increased reaction times (RTs) and increased accuracy following errors. However, although posterror slowing in combination with increased accuracy has been reported occasionally (Laming, 1968;Marco-Pallares, Camara, Münte, & Rodríguez-Fornells, 2008;Rabbitt, 1966), other studies have found posterror slowing in combination with decreased accuracy (Hajcak, McDonald, & Simons, 2003;Hajcak & Simons, 2008;Laming, 1979;Rabbitt & Rodgers, 1977).…”
mentioning
confidence: 92%
“…Research suggests that behavioral adjustment might represent a useful in error awareness. There evidences suggest a close relationship among error commission, behavioral adjustment and executive functions Marco-Pallarés et al, 2008). The awareness of errors might be the result of close engagement between executive functions and the brain EMPS.…”
Section: Error Commission: Different Types One Sourcementioning
confidence: 98%